2017
DOI: 10.14789/jmj.63.285
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Magnetic Resonance Imaging: From Isotropic Diffusion-Weighted Imaging to Diffusion Tensor Imaging and Beyond

Abstract: Diffusion magnetic resonance imaging (dMRI), which was established in the mid 1980ʼs, is an imaging technique that is based on the diffusion of water molecules in tissue. Initially it was an isotropic diffusion-weighted imaging (DWI) technique, and has been widely used mainly for investigating the tissue microstructural changes in neurological abnormalities, especially ischemic stroke. Many studies have been conducted to validate the usefulness of DWI in clinical settings and to improve the technique. Diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Andica et al investigated cognitive impairment (CI) using MRI neuroimaging and concluded that accommodation, attention, and counting were most significantly affected in moderate CI. This was also confirmed by their clinical examination of 65 ischemic stroke patients (52 men and 13 women) aged 65:6 ± 10:1 years [2]. In their research, Luong et al employed a new strategy to design a multivalent theranostic nanocarrier.…”
Section: Related Workmentioning
confidence: 78%
“…Andica et al investigated cognitive impairment (CI) using MRI neuroimaging and concluded that accommodation, attention, and counting were most significantly affected in moderate CI. This was also confirmed by their clinical examination of 65 ischemic stroke patients (52 men and 13 women) aged 65:6 ± 10:1 years [2]. In their research, Luong et al employed a new strategy to design a multivalent theranostic nanocarrier.…”
Section: Related Workmentioning
confidence: 78%